The Genesis of the Swartberg Base-Metal Sulphide Deposit, South Africa - Rudnick, Tarryn Kim (2016)
Rudnick, T.K. 2016. The Genesis of the Swartberg Base-Metal Sulphide Deposit, South Africa. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/9e9daae1-6207-4229-8bfb-61ca2729cf20